Outdoor propagation prediction for WiMAX (802.16a) signals - Thayanithy, Shivakumar (2007)
Wireless networks have emerged as a powerful architecture, capable of supporting the requirements of broadband wireless communication, with researches carried out all over the world to constantly improve the network performance and standards. Radio channel characteristics modeling is an essential in every network planning. This project deals with the performance of WiMAX networks in an outdoor environment while using the SUI channel models. The radio channel characteristics are analysed by simulations done using Matlab simulation tool. The overall system performance in terms of transmit power spectrum, receive power spectrum and bit error ratio (BER) are simulated using LabVIEW simulation tool. A qualitative performance of the system can be analysied with the help of constellation plots provided